Evidence for a cholinergic projection to neocortex from neurons in basal forebrain. - Johnston, M V (1979)
Unilateral stereotaxic injection of 3.5 nmol of kainic acid into the ventral globus pallidus of rats reduced biochemical cholinergic neuronal markers by 45-50% and virtually eliminated histochemical staining for acetylcholinesterase in neocortex ipsilateral to the lesion. At the lesion site, the large, multipolar neurons that stain densely for acetylcholinesterase were absent when compared with the uninjected side. Kainate was as effective as electrocoagulation for reducing cholinergic markers although it did not affect aminergic projections ascending through the lesioned area. The conclusion that the cholinergic projection originated in neuronal perikarya at the lesion site was supported by the failure of kainate or electrolytic lesions in contiguous regions to produce similar effects. These studies provide strong evidence for a cholinergic projection to neocortex from neurons in the forebrain in the nucleus basalis.